Pengembangan Mesin Pencacah Sampah/Limbah Plastik Dengan Sistem Crusher dan Silinder Pemotong Tipe Reel - Junaidi - -; Ichlas Nur -; Nofriadi - -; Rusmardi - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2015)
Waste plastic mounting, but can be recycled into other products in the form of granules before further processed into pellets and seed injection molding process produces products such as buckets, plates, bottles and other beverages. To be processed into the required form of granules of plastic thrasher. Though so small plastic recycling industry is still constrained in plastic enumeration process because the machine used was not optimal ability. The purpose of this research is the development of the system thrasher plastic crusher and cutter cylinder-type reel and technical evaluation. This study was conducted over two years, the first year the design and manufacture of machinery, the second year is a technical evaluation of the engine, engine performance improvements and economic analysis of granular plastic products.From the results obtained engine design capacity of the machine ± 350 kg / h, the engine size is 50 cm x 120 cm x 30 cm, power motor of 10 HP at 1450 RPM rotation with 3 phase. Some of the major components of the engine that is, counter crusher unit consists of two counter rotating cylinders opposite, counter shaft size Ø 4 cm x 58 cm, blade chopper Ø 17 cm x 2 cm with the number of teeth / blades 7 pieces and the number of blades along shaft 7 pieces, buses retaining Ø 10 cm x 2 cm. Counter-cylinder unit consists of a reel-type cutter counter shaft size Ø 4 cm x 90 cm, the middle shaft mounted cylinder with Ø 17 cm x 40 cm as the holder of the chopper blades. Chopper blade consists of 4 pieces with a size of 40 cm x 2 cm x 4 cm with ASSAB materials. Furthermore, as the blade retaining bedknife shear force of the blade chopper, upper frame, lower frame, strainer, funnel entry, exit funnel, and the drive unit consists of an electric motor, reducer, belts, pulleys and 2 pieces of gear transmission. The results of performance testing machine crusher round cylinder 75 RPM and 1450 RPM reel-type cutting machine capacity ± 300 kg / h on the filter hole Ø 1.5 cm, with a 80% grain uniformity.